CARTILHA TECNOLÓGICA SOBRE OS DIREITOS DOS PACIENTES COM DOENÇA DE ALZHEIMER - MELO, FERNANDA CORREA DE (2020)
In the areas of intellectual property there is copyright, characterized by the set of moral and patrimonial rights over the creations. Copyright is essentially linked to the innovation environment, through the development of research and / or registration of products and services. In the context of copyright and innovation, few works on the production of manuals to assist the elderly population and their caregivers with information on Alzheimer's disease were found. The objective of the research was to produce a technological booklet on the rights of the person with Alzheimer's. The technique used to produce the booklet was to review the literature on articles and legislation on the topic. Four data platforms were selected: Bireme, Lilacs, Capes and Scielo, with articles ranging from 2008 to 2018. For legal support, the Ordinances and news found in governmental electronic addresses: Ministry of Health and Legislation Portal were considered. Public Policies developed to date for Alzheimer's patients were also considered. At the end, 32 documents were analyzed in order to support the technological booklet: 21 articles, 5 Ordinances of the Ministry of Health, 2 documents with actions in Public Policies and 4 official news from the Federal Government's Legislation Portal. Data analysis was performed from the analytical and detailed reading of the material found. The results pointed out that uniting information in a technological booklet, made available electronically, will facilitate access to information about rights for both elderly people with Alzheimer's and their caregivers. In addition, the booklet will be available for free on 4 platforms: Amazon, Apple Books, Google Play and Rakuten Kobo. It is concluded that the study brought contributions to the reality of Alzheimer's patients, in order to reduce vulnerability and facilitate access to rights.